LOCAL WISDOM INTEGRATION IN LEARNING IMPLEMENTATION IN ELEMENTARY SCHOOL - Ferah Fairus; Bunyamin Maftuh; Atep Sujana; Reksa Pribadi; Fatimah Azzahra (Universitas Majalengka, 2024)
Today, the rapid development of technology and information, as well as in the agenda of welcoming society 5.0 that is in sight, positions education at the basic level to be more concerned with cultural values that are the identity of the Indonesian nation. The problem found is that cultural values have begun to fade due to the development of the times. The integration of local wisdom values in school learning should be used as sustainable development goals by many parties. The purpose of this study is to describe how local wisdom which is the identity and identity of the nation is integrated in learning in elementary schools. This research uses a qualitative approach with a literature study method of data collection techniques to explore several reputable articles related to the research. The results of this study illustrate the many ways that schools integrate local wisdom including adjustments to strengthen character education, school literacy activities, and classroom learning. Of course, the implementation of local wisdom must be strengthened by the role of teachers, the role of schools and also the role of parents who are in direct contact with students.